Inducing production rules to extend existing design grammars: The parse/derive method. Issue 4 (7th June 2017) - Eichhoff, Julian R.; Schmidt, Jens; Roller, Dieter
ABSTRACT: Graph-rewriting is a promising computation model for computer-aided design (CAD) applications that operate on graph-based design models. Graph-rewriting-based CAD systems rely on predefined production rules. These rules encode the set of possible actions that may be taken within the design process to make changes to the current design. This paper presents a method for automatically inducing new production rules from existing sample designs. The methods applicability is illustrated in context of conceptual spacecraft design. Results gained from experiments, where existing rules were deliberately left out and had to be rediscovered, show that the induced rules are often similar or identical to the original rules. GRAPHICAL ABSTRACT: